Biomechanical characteristics in freestyle - Siljeg, K.; Leko, G.; Sindik, L. (Croatian Sports Medicine Journal, 2016)
Swimming is a sport that takes place in a medium which is about 780 times denser than air, causing greater friction and greater resistance to movement of the body. During the development of the swimming sport, interdisciplinary research biomechanical laws and research in fluid dynamics, and their mutual relations are necessary. The term "freestyle", defined by FINA, imply any style that would enable the swimmer to achieve the maximum speed. Typically, swimmers in "freestyle" swim crawl. Knowing more styles and variations of the freestyle techniques, as well as freestyle elements, will enable to a swimmer a better propulsion, reducing possible injuries of the shoulder joint. Knowledge of creating propulsion throughout history has developed various modifications of the swimming freestyle technique. Preference for certain variety of the crawl for an swimmer, can enable to a coach to point out the most effective selection of distances in freestyle swimming technique (50, 100, 200, 400 or 800/1500 meters) for this swimmer. Since the arm stroke represents up to 85% of the final propulsion when swimming freestyle technique, and that the freestyle technique is most commonly used technique during the training process, knowledge of all phases of hands' work is necessary. The injury of the shoulder joint is the most common injuries in swimmers. In learning, correcting and training elements of strokes and styles of swimming, the essential assumptions and simulation tools used for the purpose of biomechanical optimization of hands' work are listed. The Index of coordination facilitates coaches to understand the individual stages of stroke, and it will certainly be of importance in the his/her direct work with the swimmer.